PENGARUH DEWAN KOMISARIS INDEPENDEN, KOMITE AUDIT, KEPEMILIKAN MANAJERIAL, UKURAN PERUSAHAAN, PROFITABILITAS, FINANCIAL LEVERAGE TERHADAP PERATAAN LABA (Income Smoothing) (Studi Empiris pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia Tahun 2013-2015) - Andani, Sri Ayu; Ritonga, Kirmizi; A, Al Azhar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study to analize the effect of independent commissioner, Audit Committe, Managerial ownership, Company Size, Profitability, Financial Leverage toward the Income Smoothing (Case Study in Manufacturing Companies listed in Indonesia Stock Exchange period 2013-2015). This study using purposive sampling technique in which this study took company data manufacturing listed on the Stock Exchange in the period 2013-2015. The population of this research were 132 companies with a selected sample of the sample is based on research criteria as many as 43 companies sampled. Multiple regrresion is used to test the hypothesis. After it was tested by using SPSS version 20. The results of this study declare that the independent commissioner and profitability has a significant impact on the income smoothing. While audit committe, managerial ownership, firm size and financial leverage has no significant effect on the income smoothing.Keywords: Income Smoothing, Good Corporate Governance, Company Size, Profitability, Financial Levergae